2018
DOI: 10.1111/rda.13371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth differentiation factor 9 and bone morphogenetic protein 15 on in vitro maturation of canine oocytes

Abstract: Contents Growth differentiation factor 9 (GDF‐9) and bone morphogenetic protein 15 (BMP‐15) have pivotal roles in oocyte development in many species, therefore the aim was to investigate these factors during in vitro maturation (IVM) of canine oocytes. Canine cumulus oocytes complexes (COCs) were cultured in six groups for 72 hr in a supplemented TCM199‐Hepes medium as (a) Control group; (b) GDF‐9 antibody (Ab); (c) BMP‐15 Ab; (d) recombinant human (rh) GDF‐9; (e) rh BMP‐15 or (f) rh BMP‐15 and GDF‐9. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…In the present study, we found a clear difference in the expression of the GDF-9 and BMP-15 genes in CCs according to the phases of the cycle, however, we did not find such differences in meiotic maturation rates (see Table 2). Meiotic development in oocytes from follicles at different estrous phases was low and within the range reported for in vitro-matured canine oocytes [12,14,27,47]. Although the percentages of MII oocytes were not different among the reproductive phases, the most remarkable result of the meiotic development analyses was the relationship of the cumulus expansion with the percentage of oocytes at the MII stage, but only during the estrus phase.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In the present study, we found a clear difference in the expression of the GDF-9 and BMP-15 genes in CCs according to the phases of the cycle, however, we did not find such differences in meiotic maturation rates (see Table 2). Meiotic development in oocytes from follicles at different estrous phases was low and within the range reported for in vitro-matured canine oocytes [12,14,27,47]. Although the percentages of MII oocytes were not different among the reproductive phases, the most remarkable result of the meiotic development analyses was the relationship of the cumulus expansion with the percentage of oocytes at the MII stage, but only during the estrus phase.…”
Section: Discussionsupporting
confidence: 73%
“…At the same time, there was a significantly lower expression of both genes in expanded CCs from IVM COCs retrieved at estrus in comparison to non-cultured COCs, suggesting that other factors possibly play a role in the meiotic stimulus at the final stage of development. However, these proteins seem to be important in acquiring meiotic competence, because the addition of recombinant GDF-9 and BMP-15 in oocyte maturation media was shown to enhance the competence of canine oocytes matured in vitro [14]. This effect is possible achieved in the early development stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GDF9 and BMP15 may cooperate in the process of oocyte meiosis resumption in dogs. Supplementing in vitro cultures with both recombinant human proteins (supplied as homodimers of the mature region) increases the rates of oocytes reaching metaphase II, while this improvement is not observed with either GDF9 or BMP15 added individually [128]. However, the pathways by which GDF9 and BMP15 may interact synergistically to improve oocyte meiosis competence is currently unknown.…”
Section: Structural Features Of Gdf9 and Bmp15 And Common Rolesmentioning
confidence: 99%